(untitled) - Abiko, M. (Centauro S.r.l.)

Endovascular Treatment for Dural Arteriovenous Fistula of the Anterior Condylar Confluence Involving the Anterior Condylar Vein: A Report of Two Cases (2008)
Anterior condylar confluence (ACC) dural arteriovenous fistula (AVF) is a rare anomaly. We describe two cases of ACC dural AVF involving the anterior condylar vein that were successfully treated with selective transvenous coil embolization. The first patient presented with headache and right pulse-synchronous tinnitus, and demonstrated abnormal flow medial to the jugular bulb within the right hypoglossal canal on source image of magnetic resonance angiography (MRA). Arterioangiography disclosed a dural AVF in this area, supplied mainly by the meningeal branches of the bilateral ascending pharyngeal artery. We diagnosed ACC dural AVF involving the anterior condylar vein and transvenous embolization was successfully performed. The second patient presented with right pulse-synchronous tinnitus. Views of source image of MRA and arterioangiography were similar to the first case and, again, transvenous embolization was successfully performed. ACC dural AVF is a rare condition and knowledge of the anatomy of the venous system around the craniocervical junction is required for successful treatment.